Estudo do comportamento de sapatas de concreto armado assentes sobre solo sedimentar da região de Santa Maria - Miozzo, Leandro Guarnieri (2007)
Superficial foundations transfer the load to soil by the distributed tensions on the base of the foundation element and, projects are normally conditioned to crack and displacement criteria. In the ordinary engineering practice, especially in the Santa Maria region, due to the absence of constitutive models and experimental data, empirical and semi-empirical models are used. In this work, we have studied the behavior of slab-on-grade concrete foundations settle on sedimentary soil at UFSM Geotechnical Engineering Experimental Field (CEEG/UFSM). The study consisted of the execution of four proofs of low loading static load on 0,60m x 0,60m slab-on-grade foundations. The resulting load-repression curves were interpreted according to prescriptions on the Brazilian norm to the obtainment of soil crack load, an the results were compared to those from other methods: theoretical, empirical, semi-empirical and correlation formulations of penetration sounding (SPT). This work was complemented by the identification of the cracking to which the soil was submitted in the research field and some concepts and methods of repression estimation and, admissible tensions. The geological and geotechnical characterization of the study place was obtained by field and laboratorial analyses performed by Emmer (2004) while the implementation of the CEEG/UFSM. The results demonstrated that the soil underwent located cracking and that theoretical and correlation methods used to estimate the cracking load value presented numbers close to those got in the field test.